A Study of Amplicor HPV DNA Detection in the ASCUS-LSIL Triage Study - Wentzensen, Nicolas (2009)
We analyzed the performance of Amplicor for detecting carcinogenic human papillomavirus infections and cervical precancer in women with an atypical squamous cells of undetermined significance (ASCUS) Pap and compared the results to Hybrid Capture 2 (hc2) in the ASCUS and low-grade squamous intraepithelial lesion (LSIL) triage study (ALTS). Baseline specimens collected from women referred into ALTS based on an ASCUS Pap result were prospectively tested by hc2 and retrospectively tested by Amplicor (n=3,277). Following receiver-operator-characteristics curve analysis, Amplicor performance was analyzed at three cutoffs (0.2; 1.0; 1.5). Paired Amplicor and hc2 results were compared for the detection of 2-year cumulative cervical intraepithelial neoplasia (CIN) grade 3 and more severe disease outcomes (CIN3+) and for the detection of 13 targeted carcinogenic HPV types. Amplicor at the 0.2 cutoff had a higher sensitivity for the detection of CIN3+ (95.8% vs 92.6%, p=0.01) but a much lower specificity (38.9% vs. 50.6%, p<0.001) than hc2. Amplicor at the 1.5 cutoff had an identical sensitivity for the detection of CIN3+ (92.6%) and a slightly lower specificity (47.5%), p<0.001). The positive predictive value of hc2 was higher at all Amplicor cutoffs, while referral rates were significantly lower (53.2% for hc2 vs. 64.1% at the 0.2 cutoff and 56.0% at the 1.5 cutoff, p<0.001). Amplicor was more analytically specific for detecting targeted carcinogenic HPV types than hc2. Amplicor at the 1.5 cutoff had comparable performance to hc2. While Amplicor missed more disease related to non-targeted types, hc2 was more likely to miss disease related to targeted types.